2021
DOI: 10.3390/antiox10010047
|View full text |Cite
|
Sign up to set email alerts
|

Role of Melatonin on Virus-Induced Neuropathogenesis—A Concomitant Therapeutic Strategy to Understand SARS-CoV-2 Infection

Abstract: Viral infections may cause neurological disorders by directly inducing oxidative stress and interrupting immune system function, both of which contribute to neuronal death. Several reports have described the neurological manifestations in Covid-19 patients where, in severe cases of the infection, brain inflammation and encephalitis are common. Recently, extensive research-based studies have revealed and acknowledged the clinical and preventive roles of melatonin in some viral diseases. Melatonin has been shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 216 publications
(269 reference statements)
0
24
0
1
Order By: Relevance
“…These include polyphenols, lipid extracts, and tomato-based nutraceuticals, all of which have been suggested for the potential prevention of cardiovascular complications of COVID-19, such as thrombosis (32,69). Melatonin is another supplement that has been identified as a potential antiviral agent against SARS-CoV-2 by computational methods (235), and it has also been highlighted as a potential therapeutic agent for COVID-19 due to its documented antioxidant, antiapoptotic, immunomodulatory, and anti-inflammatory effects (69,236,237). Notably, melatonin, vitamin D, and zinc have attracted public attention because they were included in the treatment plan of the former president of the United States upon his hospitalization due to COVID-19 (238).…”
Section: Discussionmentioning
confidence: 99%
“…These include polyphenols, lipid extracts, and tomato-based nutraceuticals, all of which have been suggested for the potential prevention of cardiovascular complications of COVID-19, such as thrombosis (32,69). Melatonin is another supplement that has been identified as a potential antiviral agent against SARS-CoV-2 by computational methods (235), and it has also been highlighted as a potential therapeutic agent for COVID-19 due to its documented antioxidant, antiapoptotic, immunomodulatory, and anti-inflammatory effects (69,236,237). Notably, melatonin, vitamin D, and zinc have attracted public attention because they were included in the treatment plan of the former president of the United States upon his hospitalization due to COVID-19 (238).…”
Section: Discussionmentioning
confidence: 99%
“…Other antioxidant compounds that have been proposed as potential adjuvants in COVID-19 are zinc [ 260 ], selenium [ 261 ], melatonin [ 262 ], curcumin [ 263 ], N-acetylcystein [ 264 , 265 ], GC4419, a SOD mimetic [ 266 ], colchicine [ 267 ], α-lipoic acid [ 268 ], glutathione [ 269 ], broccoli or glucoraphanin capsules [ 270 ], dypiridamole [ 271 ], cannabidiol [ 272 ], combinations of vitamin D, magnesium, and vitamin B12 [ 273 ], and diammonium glycyrrhizinate with vitamin C [ 274 ].…”
Section: Antioxidants As Neuroprotectors In Patients Infected With Covid-19mentioning
confidence: 99%
“…Studies in animal models demonstrate its impact in the reduction of NO and malondyaldehyde (MDA) levels as well as inducible nitric oxide synthase (iNOS) activity and apoptotic cell death during viral infections. Meningitis/encephalitis, Guillain–Barré syndrome, and hypoxic ischemia/stroke associated with SARS-CoV-2 are proposed to be treated with adequate levels of melatonin [ 262 ]. Cardinali and coworkers also propose the use of melatonin as an adjuvant for anti-SARS-CoV-2 infection treatment; the authors report that it can improve the cognitive decay observed in COVID-19 patients and during vaccination it could increase IgG antibody response and the number of CD8+ T cells [ 275 ].…”
Section: Antioxidants As Neuroprotectors In Patients Infected With Covid-19mentioning
confidence: 99%
“…As mentioned above, melatonin is an endogenous non-patentable molecule; thus, clinical trials do not expect to obtain great economic benefits; indeed, most of the clinical trials developed are public-funded [69]. To date, there is a relevant lack of clinical trials concerning melatonin s therapeutic effects versus SARS-CoV-2's directly or indirectly related pathologies [77,78]. Clinical trials are mandatory to confirm the preclinical efficacy and safety observed [79].…”
Section: Melatonin and Health: A Brief Overviewmentioning
confidence: 99%